Physical exercise and leg pain - what is the relationship? - Miranda,Patrícia (2019)
Shin splint, also known as tibial stress syndrome, results from an underlying stress reaction of the tibia caused by overuse. The patient typically refers a diffuse pain along the anteromedial side of the tibia, which is worse in late afternoon and associated with over-exercising days. Diagnosis is confirmed by a prototypical history and physical examination findings. Radiological evaluation assists in differential diagnosis. Treatment consists of adequately resting or changing training routines, together with analgesic drugs. Herein is presented the case of an adolescent referred to our Pediatric Rheumatology Unit with diffuse pain in the right pretibial region due to intensive exercise. Laboratory study and imaging exams were unremarkable. Clinical improvement following reduced exercise intensity supported diagnosis.